Implementasi Model Pembelajaran Sentra Kelas Bahan Alam untuk Pengembangan Motorik Halus Anak - 10030220029, Syafina Ramadhani Putri; Rahminawati, Nan; Sobarna, Ayi (UNISBA Press, 2024)
Abstract. Children's physical and motor growth is related to their physical growth and development. The stimulation provided by the child's environment greatly affects the child's academic achievement related to smooth muscle involvement. The center learning model, especially the natural material center at At-Taqwa Integrated Islamic Kindergarten Gegerkalong Bandung City, has activities that aim to develop children's fine motor skills. In this study, researchers used a descriptive qualitative approach with a case study method. The data collection techniques are through observation, interviews, and documentation studies. This qualitative research aims to gain detailed data and is obtained based on observations of individuals and related institutions. This research was conducted descriptively, so the researcher will explain in detail about the implementation of the center learning model in the natural material class for the development of children's fine motor skills at the At-Taqwa Integrated Islamic Kindergarten Gegerkalong Bandung City, the activities in the natural material center are very useful as training children's sensory. At-Taqwa Integrated Islamic Kindergarten which applies the center learning model in optimizing children's fine motor development is very effective because of the availability of learning media which has a major influence on aspects of child development, especially fine motor. Children will be motivated, have an interest in learning new things, because the center media used is real and interesting for children. Abstrak. Perkembangan fisik dan motorik anak berkaitan dengan pertumbuhan dan perkembangan jasmani mereka. Rangsangan yang diberikan oleh lingkungan anak sangat berpengaruh pada prestasi akademik anak terkait keterlibatan otot polos. Model pembelajaran sentra khususnya sentra bahan alam di TK Islam Terpadu At-Taqwa Gegerkalong Kota Bandung memiliki kegiatan-kegiatan yang bertujuan untuk mengembangkan motorik halus anak. Pada penelitian ini, peneliti menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Adapun teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Penelitian kualitatif ini bertujuan untuk mendapatkan data yang detail dan diperoleh berdasarkan pengamatan individu maupun Lembaga terkait. Penelitian ini di lakukan secara deskriptif, maka peneliti akan menjelaskan secara mendetail mengenai implementasi model pembelajaran sentra pada kelas bahan alam untuk pengembangan motorik halus anak di TK Islam Terpadu At-Taqwa Gegerkalong Kota Bandung, Kegiatan-kegiatan di sentra bahan alam tersebut sangat bermanfaat sebagai melatih sensori anak. TK Islam Terpadu At taqwa yang menerapkan model pembelajaran sentra dalam mengoptimalkan perkembangan motorik halus anak sangat efektif karena tersedianya media pembelajaran yang mana memiliki pengaruh besar terhadap aspek perkembangan anak terkhusus motorik halus. Anak akan termotivasi, memiliki minat untuk mempelajari hal baru, karena media sentra yang digunakan nyata dan menarik bagi anak.